A Nursery Feed for Indian Major Carps (Labeo rohita) and its Evaluation in Farmer’s Field - Das, Krushna Chandra; Mohanta, Kedar Nath; Nayak, Santosh Kumar; Mohanty, Snehalata; Sahoo, Prabin Kumar; Swain, Priyabrat (Indian Journal of Animal Nutrition, 2020)
Realizing the importance of carp feed for its nursery phase, the Fish Nutrition and Physiology Division of ICAR-CIFA, Bhubaneswar has been working since last three years and has developed a nursery feed for carp which ensured better survival, growth and palatability. The feed was prepared from maize, soybean meal, rice bran, groundnut oil cake, fish meal, oil, minerals and vitamin mixture by extrusion technology and then crumbled into suitable size for feeding the carp fry. The prepared feed was evaluated through demonstration experiments in different locations of Odisha in Government fish farm and farmer’s ponds following standard protocols. The evaluation was done in terms of growth, feed efficiency and survivability with existing feed commonly used by the farmers of the region. Result of this experiment showed that, the fish fed with developed nursery feed had 1.5 to 2 times higher growth performance, 25 percent higher survivability and better feed efficiency compared to the feed which is used by most of the farmers of this region.